Monarchs’ Names and Numbering in the Second Bulgarian State - Mladjov, Ian (Studia Ceranea, 2015)
The article explores the onomastic practices of medieval Bulgarians, focusing on the Second Bulgarian State, from the late 12th to the early 15th century. The collected evidence suggests that soon after their conversion to Christianity, Bulgarians abandoned the attested pre-Christian clan names. Yet, despite the undeniable strength of Byzantine cultural influence, neither aristocrats nor commoners in Bulgaria seem to have adopted Byzantine-type family names, nor, for that matter, making recourse to the use of patronymics as found among the Eastern and other Southern Slavs. Thus, for example, the name Asen became a true family name only among members of the royal family living in Byzantium. More generally, the few cases of family names or patronymics apparently applied to medieval Bulgarians, seem to be restricted to a foreign context. While family names and patronymics do not seem to have been employed in Christian Medieval Bulgaria, many individuals (at least where males are concerned) appear to have sported double names, composed almost invariably of a baptismal Christian name paired with a folk name usually derived from Slavic or even Bulgar tradition. This practice included Bulgaria’s monarchs, most of whom had such double names that should not be misinterpreted as family names or patronyms, as often done in the past. Specific names did, however, function as indicators for belonging within a particular lineage, as witnessed by the propagation of names like Asen, Terter, Šišman, and Sracimir. Thus, while these cannot be considered true family names, we could continue to use them as expedients to designate the ruling clans of Medieval Bulgaria (e.g., the House of Terter), albeit recognizing this to be a modern label. These considerations not only elucidate another aspect of cultural practice in Medieval Bulgaria, but also allow and necessitate a relatively inobtrusive emendation and systematization of the historiographical nomenclature of Medieval Bulgarian monarchs. Discarding the notion of family names and recognizing foreign patronymics for what they are, it becomes possible to recover the actual results of dynastic name selection, as well as the rationale behind them.